2020
DOI: 10.3390/min10030266
|View full text |Cite
|
Sign up to set email alerts
|

Two-Stage Late Jurassic to Early Cretaceous Hydrothermal Activity in the Sakar Unit of Southeastern Bulgaria

Abstract: Southeastern Bulgaria is composed of a variety of rocks from pre-Variscan (ca. 0.3 Ga) to pre-Alpine sensu lato (ca. 0.15 Ga) time. The Sakar Unit in this region comprises a series of granitoids and gneisses formed or metamorphosed during these events. It is cut by a series of post-Variscan hydrothermal veins, yet lacks pervasive Alpine deformation. It thus represents a key unit for detecting potential tectonism associated with the enigmatic Cimmerian Orogenic episode, but limited geochronology has been undert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 51 publications
0
5
0
2
Order By: Relevance
“…1; Bonev et al, 2021). All these rocks have been metamorphosed at upper greenschist to amphibolite facies metamorphism during latest Jurassic to Early Cretaceous times (Neubauer et al, 2010;Vladinova et al, 2019;Szopa et al, 2020;Bonev et al, 2020). An earlier, Variscan metamorphic event is also suggested for the older rocks of this unit, in comparison with similar metamorphic rocks from the Strandzha Zone in Turkey (e.g., Okay et al, 2001;Sunal et al, 2011;Sałacińska et al, 2022).…”
Section: Sakarmentioning
confidence: 86%
See 1 more Smart Citation
“…1; Bonev et al, 2021). All these rocks have been metamorphosed at upper greenschist to amphibolite facies metamorphism during latest Jurassic to Early Cretaceous times (Neubauer et al, 2010;Vladinova et al, 2019;Szopa et al, 2020;Bonev et al, 2020). An earlier, Variscan metamorphic event is also suggested for the older rocks of this unit, in comparison with similar metamorphic rocks from the Strandzha Zone in Turkey (e.g., Okay et al, 2001;Sunal et al, 2011;Sałacińska et al, 2022).…”
Section: Sakarmentioning
confidence: 86%
“…Papanikolaou (2009), and later Schenker et al (2014Schenker et al ( , 2015, suggested the existence of two distinct Late Jurassic-Early Cretaceous tectono-metamorphic events, related to northward subduction of Vardar and overall collision, first in the Rhodope peaking at 150 Ma to 130 Ma and later in Pelagonia at 130 Ma to 110 Ma. Several authors also report two metamorphic events, one in the Late Jurassic-Early Cretaceous and the other in the late Early Cretaceous, in the Strandzha and Sakar units based on geochronological and P-T condition analysis (Lilov et al, 2004;Elmas et al, 2011;Szopa et al, 2020). The fact that the events in Strandzha and Sakar are not related to HP conditions suggests that, although contemporaneous to those in the Rhodope, they were not associated with subduction of these units as those from the Intermediate Terrane.…”
Section: Late Jurassic To Early Cretaceous Metamorphismmentioning
confidence: 99%
“…The temperature of chlorite growth was calculated using three various empirical chlorite geothermometers proposed by Cathelineau and Nieva ( 1985 ), Kranidiotis and MacLean ( 1987 ), and Jowett ( 1991 ), which are well suited to constraining chlorite temperatures in various geological environments (e.g. Janeczek et al 2020 ; Szopa et al 2020 ). The temperatures obtained by the various chlorite geothermometers in the porphyroids range from 280 to 360 °C (Table 3 ), which is in agreement with the phase diagram constraints (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Chatalov, 1990). All these units are penetratively deformed and metamorphosed during the Late Jurassic to Early Cretaceous Early Alpine Orogeny (Chatalov, 1988(Chatalov, , 1990Gerdjikov 2005;Bonev et al 2020b;Szopa et al 2020). The highest grades (amphibolite-facies) associated with Early Alpine metamorphism are encountered in the Sakar Mountains (Chatalov, 1990;Tsankova & Pristavova 2007a, b) and in the Harmanli Block (Jordanov et al 2008) of the Sakar Unit.…”
Section: B Evolution Of the Units And The Granitoidsmentioning
confidence: 99%